Environmental issues in Malaysia: suggestion to impose carbon tax / Norfakhirah Nazihah Mohd Hasnu and Izlawanie Muhammad - Nohd Hasnu, Norfakhirah Nazihah; Muhammad, Izlawanie (Accounting Research Institute (ARI), 2022)
Malaysia has a long history of environmental issues. The Malaysian government has implemented deterrent and supportive strategies to reduce the issue by penalising polluters and providing tax incentives to encourage green technology developments. However, these strategies are ineffective since the number of pollution issues keeps increasing, and the Malaysia Environmental Performance Index (EPI) 2020 score has dropped. Many countries have implemented carbon tax to mitigate some environmental issues following the recommendation by the Organization for Economic Co-operation and Development. The carbon tax has proven to be an effective strategy not only to reduce environmental problems but also to increase government revenues. This conceptual paper aims to give a brief review of literature for future studies in implementing a carbon tax policy in Malaysia. It is hoped that the findings will assist the Malaysian government in implementing a carbon tax policy to reduce environmental issues and as a strategy to widen its tax base.